Efficacy of an acoustic hailing device as an avian dispersal tool - Peter E. Schlichting; Amanda E. Holland; James C. Beasley; Albert L. Bryan; Robert A. Kennamer; Travis L. DeVault; Bradley F. Blackwell; Olin E. Rhodes Jr. (Wildlife Society Bulletin)
ABSTRACT Bird strikes are a major safety and financial concern for modern aviation. Audible stimuli are common bird dispersal techniques, but their effectiveness is limited by the saliency and relevance of the stimulus. Furthermore, high ambient sound levels present at airfields might require that effective audible stimuli rely more on total volume (i.e., exceeding physiological tolerances) than ecological relevance. Acoustic hailing devices (AHD) are capable of sound output with a narrow beam width and at volumes high enough to cause physical discomfort at long distances. We tested the effectiveness of an AHD as a dispersal tool on free‐ranging birds recognized as hazardous to aviation safety at the Savannah River Site and Phinizy Swamp Nature Park in South Carolina and Georgia, USA, respectively, between October 2013 and March 2015. Our study design included experimental trials with timed‐interval counts of birds directly before and after AHD treatment. For most species, counts of birds associated with treatment periods (use of AHD) and control periods (no use of AHD) occurred on different days. Sound treatments yielded variable success at dispersing birds. Specifically, AHD treatment was effective for dispersing vultures (Coragyps atratus and Cathartes aura) and gulls (Laridae), but ineffective for dispersing blackbirds (Icteridae), diving ducks (Aythya spp., Bucephala spp., Oxyura spp.), and coots (Fulica americana). Trials were conducted in a relatively quiet environment with birds that were unhabituated to excessive noise; thus, we cannot unequivocally recommend an AHD as a universally effective avian dispersing tool. However, future research should consider AHD testing integrated with other methods, as well as investigation of treatments that might be salient to specific target species. © 2017 The Wildlife Society.